PERSPEKTIF ULAMA TENTANG KEWIRAUSAHAAN MUSLIM (STUDI EMPIRIS DI INDONESIA) - Faisal Muttaqin (JURNAL AGHNIYA, 2022)
AbstractThe purpose of this study is to analyze the criticality of the notion of Islamic entrepreneurship. Most likely the attention paid to Islamic entrepreneurship is not enough. This paper attempts to explain this problem. The method used in this study is a combination of a critical study of contemporary research and an empirical analysis of the ulama's perception of Islamic entrepreneurship in Indonesia. The results show that Islamic standards, viewpoints, practices, and entrepreneurship actually influence. This paper recommends several research perspectives. In addition, it can support state- owned and private companies to accelerate entrepreneurship.Key Words:Enterpreneurship, Ulama, Islamic Value